PENERAPAN MODEL PEMBELAJARAN SEARCH, SOLVE, CREATE, AND SHARE UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA - Musdalifa Musdalifa (Prodi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Muhammadiyah Parepare, 2025)
This research constitute action research brazes (Classroom Action Research) one that intent to increase mathematics studying result via implemented model learning search, solve, create, and share on classes educative participant VIII.2 SMP is Country 2 Suppa. Subject is this research is participant teach to braze VIII.2 SMP is Country 2 Suppa that total 22 person. This research is done in two cycle which on cycle I consisting of thrice meet learning process and once appointment is done essays cycle whereas on cycle II consisting of thrice meet learning process and once appointment essays cycle. Data collecting tech that is utilized in this research which is data about studying result took by gives essay each cycle final, meanwhile data about teacher activity and participant activity teach by use of been taken observation sheet upon happens it learning process at within class. Base observational result and study up to two cycles, therefore gets to be concluded that mathematicses learned result participant be taught by class VIII.2 SMP is Country 2 Suppa experiences step-ups of cycles I go to cycles II. It pointed out by: (1) increases it average usufructs participant mathematics studying be taught which is 55 on cycle I as 82,68 on cycle II; (2) increases it average participant activity percentage is taught suitably learning which is 32,24% on cycle I to increase becomes 43,07% on cycle II and increases it average ability percentage learns in activity learning of cycle I goes to cycle II which is 2,71% worked up as 3,09% and (3) increases it participant percentage are taught that complete learned which is 31,8% on cycle I as 90,9% on cycle II.